2020
DOI: 10.1111/jdi.13397
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the effects of pre‐transplant diabetes on mortality and cardiovascular events after kidney transplantation

Abstract: Aims/Introduction: It is not clear whether survival in kidney transplant recipients with pre-transplant diabetes has improved over the past decades. We compared the rates of mortality and major adverse cardiovascular events (MACE) after renal transplantation in patients with and without pre-transplant diabetes. Furthermore, we investigated whether transplant era and recipient age affected the association between diabetes status and adverse events. Materials and Methods: This retrospective cohort study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Gaynor et al [6] suggested that the time taken for PTDM to negatively influence KT outcomes is considerable. In this context, we reported, in a cohort study, that pretransplant diabetes, which implies a longer exposure to chronic hyperglycemia than PTDM, was a risk factor for four-point MACE and posttransplant mortality [4]. The present study suggests that PTDM patients with long duration diabetes have a significantly elevated risk of CVD.…”
Section: Article In Presssupporting
confidence: 51%
See 1 more Smart Citation
“…Gaynor et al [6] suggested that the time taken for PTDM to negatively influence KT outcomes is considerable. In this context, we reported, in a cohort study, that pretransplant diabetes, which implies a longer exposure to chronic hyperglycemia than PTDM, was a risk factor for four-point MACE and posttransplant mortality [4]. The present study suggests that PTDM patients with long duration diabetes have a significantly elevated risk of CVD.…”
Section: Article In Presssupporting
confidence: 51%
“…Post-transplant diabetes mellitus (PTDM), i.e., diabetes newly detected after transplantation, is a common complication (incidence of 10% to 25%) [2][3][4]. PTDM is associated with a poor prognosis after KT [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…DM is known to be an important risk factor for chronic kidney disease and end-stage renal disease (ESRD) [ 3 ]. Indeed, almost 20–38% of patients undergoing kidney transplantation have DM [ 4 , 5 ]. However, a significant proportion of patients are known to develop DM after organ transplantation as well.…”
Section: Introductionmentioning
confidence: 99%
“…22 Pre-transplant diabetes was associated with an increased risk of postoperative mortality (HR 1.9, 95% CI 1.05-3.44) and MACEs (HR 1.75, 95% CI 1.02-3.00). 23 De Lima et al reported that cardiovascular events within a 12-month post-transplant period were associated with a 55% mortality rate. 22 Despite the strong evidence for increased risk of MACEs in KT recipients, preoperative cardiac risk reduction for the general population may be less effective for the KT population.…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…22 Pre-transplant diabetes was associated with an increased risk of postoperative mortality (HR 1.9, 95% CI 1.05–3.44) and MACEs (HR 1.75, 95% CI 1.02–3.00). 23 De Lima et al reported that cardiovascular events within a 12-month post-transplant period were associated with a 55% mortality rate. 22…”
Section: Kidney Transplantation (Table 1)mentioning
confidence: 99%